Factors and Lattice Reactions Governing Phase Transformations in Beta Phase Alloys - Adiguzel, O. (Springer Science+Business Media B.V., 2020)
Metals and alloys have different phases at different conditions in crystallographic basis, and these phases are described in phase diagrams as alloy composition-temperature, or composition-pressure dependent. Beta phases of alloys mainly have bcc-based ordered or disordered structure and these phases are very sensitive to external conditions, and phase structures turn into other crystal structures by lowering temperature and stressing material, by means of dual thermal and stress induced martensitic transformations. Lattice vibrations and interatomic interactions play an important role in the processing of transformation. Thermal induced martensitic transformation occurs in atomic scale in the material on cooling from parent phase region, and interatomic interactions govern this transition. These interactions are described by pair-wise potential function between all of the atom pairs, and embedded atom electron cloud potential functions. Thermal induced martensitic transformation occurs along with lattice twinning on cooling and ordered parent phase structures turn into twinned martensite structures, these structures turn into detwinned martensite structures by stressing material by means of strain induced martensitic transformation. Thermal induced martensitic transformation occurs as a lattice reaction with the cooperative movement of atoms on two opposite two opposite directions, ?110?-type directions on the {110}-type planes of austenite matrix which is basal plane of martensite. Copper based alloys exhibit this property in metastable ?-phase region, which has bcc-based structures at high temperature parent phase field. Lattice invariant shear and twinning is not uniform in these alloys and gives rise to the formation of complex layered structures. In the present contribution, X-ray diffraction and transmission electron microscopy (TEM) studies were carried out on two copper based CuAlMn and CuZnAl alloys, and reached results were interpreted. © 2020, Springer Nature B.V.
Keywords: Detwinning; Lattice twinning; Martensitic transformations; Shape memory effect